A Late Jurassic deep-bodied actinopterygian from Antarctica - Gouiric Cavalli, Soledad (2024)
Mesozoic deep-bodied actinopterygians are of interest given, among others, the various modes of feeding exhibited by these fishes. Regrettably, most of their fossil record is restricted to a limited number of localities in Europe. During the Late Jurassic fragmentation of Pangaea, the exchange of fauna between the European Tethys and the paleo-Pacific (southwestern of the South American region) was possible via the marine pathways connecting these areas. This ex- change led to the speciation of fish taxa, particularly in the Southern Hemisphere. Although new species are continuously being discovered, our understanding of the Late Jurassic marine ichthyofaunas of the Southern Hemisphere remains limited. The Mesozoic ichthyofaunas of the Antarctic seas are rich but relatively poorly known presenting a significant opportunity for further research. Noteworthy, previous reports have documented the presence of actinopterygians in the Late Jurassic of the Antarctic Peninsula. Since 2016, a team of researchers from Argentina has been exploring the Upper Jurassic–Lower Cretaceous Ameghino (= Nordenskjöld) Formation outcrops, resulting in the discovery of a large collection of actinopterygian fishes. Nevertheless, most of the material remains undescribed. In this article, we report the discovery of a deep-bodied actinopterygian found at the Longing Gap, the type locality of the Ameghino Formation in the Antarctic Peninsula. The study of these newly collected materials allows for their taxonomic assignment to Ameghinichthys antarcticus, a taxon previously described for the locality but based on isolated and fragmentary material. Additionally, this study confirms that A. antarcticus belongs to Dapediiformes. Ameghinichthys antarcticus is among the youngest records of Dapediiformes and represents the southernmost record of the group worldwide.